Effect of Work Motivation, Physical Work Environment and Organizational Culture on Employee Performance at PT Binajasa Abadikarya Jakarta - Saputri, Zahwa Assabilliyah; Karyatun, Subur; Digdowiseiso, Kumba (International Journal of Social Service and Research, 2024)
This study aims to assess the impact of Work Motivation, Physical Work Environment, and Organizational Culture on Employee Performance at PT Binajasa Abadikarya Jakarta. Recognizing the critical role of employee performance in organizational success, this research endeavors to shed light on the specific factors that contribute to or hinder it. The study employed a primary data collection method, utilizing questionnaires distributed to 160 respondents. The analysis was conducted using multiple linear regression analysis through the Statistical Product and Service (SPSS) version 25. The findings indicate that Work Motivation (X1) and Organizational Culture (X3) exhibit a positive and significant influence on employee performance. Surprisingly, the Physical Work Environment variable (X2) did not show a significant effect on employee performance. PT Binajasa Abadikarya must consider these results seriously, as they suggest the need for targeted interventions in the realms of Work Motivation and Organizational Culture. While Physical Work Environment may not have demonstrated a significant impact in this study, future investigations could delve deeper into this aspect. The study timeframe and sample size should be considered when interpreting the results, and recommendations are proposed for PT Binajasa Abadikarya to focus on enhancing Work Motivation, Organizational Culture, and further exploration of the Physical Work Environment to optimize overall employee performance. This research contributes to the broader understanding of factors influencing employee performance and provides practical insights for organizational improvement strategies.